Self-assembly and on-surface chemistry of tetraphenyl porphyrin - Frampton, Eleanor (2021)
Self-assembly of molecular building blocks to produce extended two-dimensional arrangements is a first step on the journey towards the design and construction of molecular systems with a predictable structure and functionality. By employing scanning probe techniques such as scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS), an understanding of these self-assembled structures on the single-molecule level can be obtained. When combined with other techniques such as x-ray photoelectron spectrocopy (XPS) and x-ray standing wave analysis (NIXSW), the adsorption geometries and reaction pathways can be extracted to give a completed picture of each system.